Influence of Major Histocompatibility Complex on Bacterial Composition of Fecal Flora - Toivanen, Paavo (American Society for Microbiology, 2001)
Very little is known about how the host genome influences the composition of the gastrointestinal flora, largely due to the great number and diversity of bacteria present in the flora and the difficulties of using traditional methods of bacterial isolation and identification. We have approached the problem by studying bacterium-derived cellular fatty acids in the stool samples of six mouse strains congenic for the major histocompatibility complex (MHC). The results obtained indicate that the composition of the fecal flora is genetically regulated. In addition to undefined gene loci, MHC alone has a pronounced effect, since mice with different MHC in the same background have significantly different fecal floras. Demonstration of the genetic influence on the gastrointestinal flora opens a new approach to studying the pathogenesis of bacterially induced diseases.